2009
DOI: 10.1073/pnas.0906925106
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput in vivo screening of targeted molecular imaging agents

Abstract: The rapid development and translation of targeted molecular imaging agents from bench to bedside is currently a slow process, with a clear bottleneck between the discovery of new compounds and the development of an appropriate molecular imaging agent. The ability to identify promising new molecular imaging agents, as well as failures, much earlier in the development process using high-throughput screening techniques could save significant time and money. This work combines the advantages of combinatorial chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 40 publications
1
65
0
Order By: Relevance
“…Structural analyses of FMDV and FMDV-derived peptides have shown that the integrin-binding loop consists of a short region of a ␤-strand followed by the RGD, which is in turn is followed by a helical structure (16,(18)(19)(20)(21)(22). Typically, native ligands for ␣v␤6 have leucine (L) or methionine (M) at the RGD ϩ1 site and leucine or isoleucine (I) at the RGD ϩ4 site (16,23,24). FMDV may be highly adapted to use ␣v␤6 as a receptor, as it has a similar conserved sequence (L, M, or arginine at the RGD ϩ1 site and L or I at the RGD ϩ4 site) following the RGD.…”
mentioning
confidence: 99%
“…Structural analyses of FMDV and FMDV-derived peptides have shown that the integrin-binding loop consists of a short region of a ␤-strand followed by the RGD, which is in turn is followed by a helical structure (16,(18)(19)(20)(21)(22). Typically, native ligands for ␣v␤6 have leucine (L) or methionine (M) at the RGD ϩ1 site and leucine or isoleucine (I) at the RGD ϩ4 site (16,23,24). FMDV may be highly adapted to use ␣v␤6 as a receptor, as it has a similar conserved sequence (L, M, or arginine at the RGD ϩ1 site and L or I at the RGD ϩ4 site) following the RGD.…”
mentioning
confidence: 99%
“…In this strategy, the selected amino group is unprotected and the otherwise protected peptide is labeled site-specifically on solid phase then cleaved from the resin and deprotected and purified. The solid phase radiolabeling approach is very robust and a wide variety of 18 F-labeled peptides could be obtained with minimal optimization of the radiolabeling procedure [22]. Because the solid phase approach is time consuming and the overall yield is generally inversely proportional to the size of the peptide faster and more efficient methods for 18 F-fluorination of peptides have been sought.…”
Section: Peptide Based Probes For Immunopetmentioning
confidence: 99%
“…An effective answer to this request can be found through the in vivo screening tests of targeted molecular imaging agents. For example, Gagnon et al [3] demonstrated the feasibility of a high-throughput in vivo screening approach using animal imaging for 18 F peptides.…”
Section: Which Peptide? Which Chemical Form? Which Tracer?mentioning
confidence: 99%